Development of a novel polyethersulfone ultrafiltration membrane with antibacterial activity and high flux containing halloysite nanotubes loaded with lysozyme - Zhao, Q.; Liu, C.; Liu, Jian; Zhang, Y. (Royal Society of Chemistry, 2015)
In this study, halloysite nanotubes (HNTs) were used to immobilize lysozyme via a covalent binding reaction. Immobilized lysozyme (HNTs-Ly) was then added to a polyethersulfone (PES) polymer solution to prepare hybrid antibacterial ultrafiltration membranes via classic phase inversion. The results showed that the surface hydrophilicity and the water flux of the hybrid membranes were significantly improved after adding HNTs-Ly. When the content of HNTs-Ly was 3.0 wt%, the water flux of the resultant membranes could achieve values as high as 400 L m-2h-1and maintain higher rejections for PEG 20000 (69%) and PVA 30000-70000 (99.6%). The tensile strength and the elongation at the break of the hybrid membranes were increased after adding HNTs-Ly, which revealed that the mechanical strength of the membranes was also enhanced. Moreover, the hybrid membrane showed a good antibacterial activity against Gram-negative bacteria (E. coli) with a high bacteriostasis rate of 63%. This journal is